Eksplorasi Gaya Belajar, Efikasi Diri dan Intensitas Belajar Mahasiswa pada Kegiatan Site Visit Survey Learning - Slamet, Slamet (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were: (1) to determine learning styles, self-efficacy and learning intensity of the students in the course of Instrumentation Practicum, and (2) to analyse their correlation through the Site Visit Survey Learning. This study employed the ex-post facto method. The descriptive analysis of the data revealed: (1) the students’ learning styles showed an inclination to dominant accommodative, the students’ self-efficacy were mostly categorised as high with the percentages of 56%. The students’ learning intensity categorised as high and  low were 36% and 32% respectively; and (2) there is a positive and significant correlation between self-efficacy and learning intensity with the coefficient of  0.446 (p = 0.025). The learning style of Active Experimentation (AE) has a positive but not significant correlation with the learning intensity with the coefficient of 0.305 (p = 0.139). While the learning styles of Reflective Observation (RO),Concrete Experience (CE) and Abstract Conceptualisation (AC)  have the coefficients of correlation  with  learning intensity  that were r = ̶ 0.305 with p = 0.139, r = ̶ 0.061 with p = 0.771 and r = + 0.061 with p = 0.771 respectively.